Pharmaceutical care during COVID-19 pandemic: challenges and perspectives - Thais Rodrigues Penaforte (Universidade de São Paulo, 2022)
Abstract COVID-19 (SARS-CoV-2) pandemic is raising many questions about the future of face-to-face interactions. The possible changes on healthcare delivery may provoke a long term disruption on pharmaceutical assistance requiring new approaches to provide pharmaceutical services. The proposal of pharmaceutical care is patient oriented, and its activities include different forms of interaction. The emergence of COVID-19 puts to the test all the efforts to reposition pharmaceutical care in the set of clinical activities. Now, the pharmaceutical consultations and group activities, which played a fundamental role in the reformulation of pharmacy practices, must be revised in order to reduce the risk of patient agglomeration and contamination. Several researchers suggest technology use to intermediate health care assistance. However, few studies had rigorously analyzed the effectiveness of virtual health care on the pharmaceutical field. Innovating the pharmacy workflow, during the course of a crisis like COVID-19, is the current challenge addressed to all pharmacists. This unforeseen situation requires us to reconsider our plans and actions. It will be necessary resilience, courage and creativity to achieve a consistent attitude, which provides a quick response to the health care needs in this time of crisis.